EVALUASI KINERJA ANGKUTAN UMUM TRAYEK MALANG – KEDIRI BERDASARKAN KEPUASAN PELAYANAN PADA MASA PANDEMI COVID-19 - Rifky Aldila Primasworo; Galih Damar Pandulu; Yusta Dayuwasti Gons (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract Public transportation for passengers on the Malang - Kediri route is a transportation that serves between cities within the province, and this route is one of the very long routes with a travel time of ± 4 hours. Over time, planners sometimes need to re-evaluate the performance of Bus transportation to meet the standard values of the Land Transportation Service. The purpose of this study is to determine the performance of public transport services, public transport productivity, and to make alternative solutions related to the results of performance evaluation of public transport services. In this study, the assessed public transport performance indicators are load factor, headway, frequency, number of operating vehicles, travel speed, service time, waiting time, travel time, and also indicators of service satisfaction assessed are physical evidence, reliability, responsiveness, assurance, empathy. Indicators - These indicators are obtained from the results of dynamic surveys and static surveys. From the results of the evaluation of public transport service standards according to the Director General of Land Transportation, the performance of the Malang - Kediri route public transport is in the medium category. There are 4 factors for the satisfaction of passengers who have services with a high level of importance and low performance, while 15 other factors have a good / high level of importance and performance. The productivity of the Malang - Kediri route public transport is 31 pnp / day-vehicle. Alternative solution given is: improving service performance by repairing services that are not in accordance with service standards, and supported by the participation of the Government as policy makers and decisive action for violations of service standards, especially city transportation services. Keywords: evaluation, public transportation performance, service.